2015
DOI: 10.1519/jsc.0000000000000623
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Differences Between Boys and Girls Result in Sex-Specific Physical Fitness Changes From Fourth to Fifth Grade

Abstract: To better understand how developmental differences impact performance on a broad selection of common physical fitness measures, we examined changes in boys and girls from fourth to fifth grade. Subjects included 273 boys (age, 9.5 ± 0.6 years; height, 139.86 ± 7.52 cm; mass, 38.00 ± 9.55 kg) and 295 girls (age, 9.6 ± 0.5 years; height, 139.30 ± 7.19 cm; weight, 37.44 ± 9.35 kg). We compared anthropometrics, cardiorespiratory and local muscular endurance, flexibility, power, and strength. A mixed-method analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
4
11
0
Order By: Relevance
“…In our study, cardiorespiratory fitness significantly decreased over 2 years in girls and increased slightly in boys, although only the changes in girls showed significant statistical difference. Our results are similar to other studies (Catley & Tomkinson, ; Ferrari, Bracco, Matsudo, & Fisberg, ; Flanagan et al, ; Marta, Marinho, Barbosa, Izquierdo, & Marques, ; Santos et al, ), particularly an eight‐year follow‐up study of 86 Portuguese children (44 girls) from the European Youth Heart Study, which showed that cardiorespiratory fitness significantly increased in boys and decreased in girls (Ornelas, Silva, Minderico, & Sardinha, ).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, cardiorespiratory fitness significantly decreased over 2 years in girls and increased slightly in boys, although only the changes in girls showed significant statistical difference. Our results are similar to other studies (Catley & Tomkinson, ; Ferrari, Bracco, Matsudo, & Fisberg, ; Flanagan et al, ; Marta, Marinho, Barbosa, Izquierdo, & Marques, ; Santos et al, ), particularly an eight‐year follow‐up study of 86 Portuguese children (44 girls) from the European Youth Heart Study, which showed that cardiorespiratory fitness significantly increased in boys and decreased in girls (Ornelas, Silva, Minderico, & Sardinha, ).…”
Section: Discussionsupporting
confidence: 92%
“…Grip strength by body weight status among U.S. youth was recently reported, but findings were limited to mean values for boys and girls aged 6-15 years and did not provide percentile information for children (10). Recent data on changes in grip strength from fourth to fifth grades showed small increases for the girls but not for the boys from year to year (12). Normative grip strength estimates have also been reported for Canadian men and women across age groups, and additionally, grip strength cut points corresponding to health benefit zones (HBZs) have been established (4,5,33).…”
Section: Introductionmentioning
confidence: 99%
“…Marta et al found that boys demonstrated higher aerobic fitness, speed, and strength and girls had higher flexibility scores [48]. Flanagan et al similarly found that boys' cardiorespiratory endurance and power performance was higher than for girls in both the fourth and fifth grades [49]. Moreover, Messiah et al found that boys aged 9-16 had significantly higher fitness scores compared with girls for the PACER, sit-up and push-up tests [50].…”
Section: Plos Onementioning
confidence: 99%